STROKES DURING SLEEP AND WAKEFULNESS: CLINICAL, PATHOLOGICAL AND STATISTICAL ANALYSIS - Sobirov , Javlon (Uzbekistan Open Conference, 2025)
This article discusses the pathogenesis, clinical manifestations, diagnostic methods, and approaches to the treatment of strokes that occur during sleep. Statistics of patients observed between 2022 and 2024 are analyzed. Based on the results of the research, recommendations are developed.
Keywords: stroke; ischemic stroke; sleep stroke; apnea syndrome; MRI; thrombolytic therapy; statistical analysis